Incentive regulation, investments and technological change - Ingo Vogelsang (Center for Economic Studies and ifo Institute (CESifo), 2010)
Based on an idiosyncratic reading of the literature I propose intermediate (rather than tight or soft) regulation for balancing investment incentives with allocative efficiency and competition objectives. Intermediate regulation is compatible with incentive regulation and helps lengthening the regulatory commitment period necessary for incentives. However, such commitment for the whole time horizon of infrastructure or innovation investments is impossible. The compatibility of incentive regulation and efficient investment is thus in doubt. Incentive regulation for regular infrastructure investments therefore needs periodic updating based on rate-of-return regulation criteria. Innovative infrastructure investments may warrant regulatory holidays, which should be conditioned on strict criteria.
Keywords: L50; L90; 330; Anreizregulierung; Investitionspolitik; Infrastrukturinvestition; Innovation; Allokationseffizienz; Theorie